THE QUANTITATIVE CASE-BY-CASE ANALYSES OF THE SOCIO-EMOTIONAL OUTCOMES OF CHILDREN WITH ASD IN ROBOT-ASSISTED AUTISM THERAPY - Telisheva, Zhansaule; Amirova, Aida; Rakhymbayeva, Nazerke; Zhanatkyzy, Aida; Sandygulova, Anara (Multimodal Technologies and Interaction, 2022)
With its focus on robot-assisted autism therapy, this paper presents case-by-case analyses of socio-emotional outcomes of 34 children aged 3–12 years old, with different cases of Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD).We grouped children by the following characteristics: ASD alone (n = 22), ASD+ADHD (n = 12), verbal (n = 11), non-verbal (n = 23), low-functioning autism (n = 24), and high-functioning autism (n = 10). This paper provides a series of separate quantitative analyses across the first and last sessions, adaptive and non-adaptive sessions, and parent and no-parent sessions, to present child experiences with the NAO robot, during play-based activities. The results suggest that robots are able to interact with children in social ways and influence their social behaviors over time. Each child with ASD is a unique case and needs an individualized approach to practice and learn social skills with the robot. We, finally, present specific child–robot intricacies that affect how children engage and learn over time as well as across different sessions.
Keywords: Type of access: Open Access; robot-mediated therapy; ASD; individual differences; parental presence; adaptivity